PERSEPSI KHALAYAK TENTANG KASUS PENYERBUAN FPI KE KANTOR TEMPO TERKAIT KARIKATUR PRIA BERSORBAN DI KOLOM KOMENTAR YOUTUBE - Hanny Nurmalita Anggadewi; Nurul Hasfi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This research was motivated by the extreme protest of a community organization called Front Pembela Islam (FPI) to the Tempo office due to publication of turbaned man caricatures in Tempo Magazine. This study aims to identify how public perceptions of turbaned man caricature cases in the YouTube comments column to be examined from the point of view of public sphere. This research was conducted using descriptive qualitative methods and verbal data analysis. To answer the research question, researcher used the New Media Theory of McMillan, Sally J., the concept of Public Sphere Jurgen Habermas and The Freedom of Expression concept. This study found that there are four main perceptions, namely Positive Perception of Tempo, Negative towards Tempo, Positive towards FPI and Negative towards FPI. These four perceptions have a relevance level of comments varying from high to moderate and also category of irrelevant comment. From the data above, this study concludes that the comment column on YouTube is not public space as explained in the concept of Habermas Public Sphere.